A Case Series of Verucca Vulgaris Treated with Homoeopathic Similimum (Advancements in Homeopathic Research, 2023)
Warts are benign cutaneous and mucosal lesions.  The human papillomavirus (HPV) causes warts, and  there are over 100 different forms of HPV. HPV can  be found anywhere. Although many Homoeopathic  medicines may be found in therapeutics of warts but  through this case , once again it has been proved that  Homoeopathic medicines acts best when prescribed  on the basis of individualisation that too quickly.
Keywords: Warts; human papilloma viruses (HPVs); homoeopathic treatment; individualization; similimum